Ответ:
1 -2, 2 -12, 3 -24, 4 -4.
Пошаговое объяснение:
1.
1) 63+27=90
2) 90:9=10
3) 10:5=2
2.
1) 27:9=3
3) 63-3=60
3) 60:5=12
3. 72:6.2 ??? Норм напиши
Если 72:6*2, то
1) 72:6=12
2) 12*2=24
4.
1) 6*3=18
2) 72:18=4
{a-b=√6 => a=√6+b
{a+b=√10
√6+b+b=√10
2b=√10-√6
b=(√10-√6)/2
a=√6+((√10-√6)/2)
2a=2√6+√10-√6
a=(√6+√10)/2
a*b=(√6+√10)/2*(√10-√6)/2
(√6√10-6+10-√10√6)/2=
4/2=2
Ответ:a*b=2
Это элементарно! тут просто есть ответ и его надо найти!
12+18=30 мин потратил на весь путь задача решается схемой